2017
DOI: 10.3758/s13415-017-0536-6
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of conventional and harm/welfare-based moral decision-making

Abstract: The degree to which social norms are processed by a unitary system or dissociable systems remains debated. Much research on children’s social-cognitive judgments has supported the distinction between “moral” (harm/welfare-based) and “conventional” norms. However, the extent to which these norms are processed by dissociable neural systems remains unclear. To address this issue, 23 healthy participants were scanned with functional magnetic resonance imaging (fMRI) while they rated the wrongness of harm/welfare-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 94 publications
1
9
0
Order By: Relevance
“…This relation is affected by the reaction of the amygdala to pain signals. 43 In short, a weak reaction ability to others' pain is correlated to a reduced sense of guilt and empathy and a rise in instrumental aggression. Functional magnetic resonance imaging research indicates that the amygdala is one of the core regions for moral judgment and is always in an active state in moral judgment tasks.…”
Section: Discussionmentioning
confidence: 99%
“…This relation is affected by the reaction of the amygdala to pain signals. 43 In short, a weak reaction ability to others' pain is correlated to a reduced sense of guilt and empathy and a rise in instrumental aggression. Functional magnetic resonance imaging research indicates that the amygdala is one of the core regions for moral judgment and is always in an active state in moral judgment tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Blair and his colleagues (White, Leong, Smetana, Nucci, & Blair, 2013) have recently used fMRI techniques to demonstrate both similarities and differences in the brain regions activated when normal, healthy adults made judgments about moral (welfare and harm-based) and conventional transgressions. Blair et al (2013) observed increased neural activation in the amygdala and ventromedial prefrontal cortex when adults rated harm-based transgressions as compared to conventional transgressions, but there was also activation in several regions in the frontal cortex when adults processed both types of transgressions. These findings provide interesting new evidence regarding distinctions between morality and social convention, specifically that judgments about morality involve both emotion and cognition.…”
Section: Neuroscience Of Moral and Conventional Judgmentsmentioning
confidence: 99%
“…Moral transgressions are generally judged by neurotypical (NT) children as more serious and less permissible than conventional transgressions [ 4 , 14 ]. A recent neuroimaging study revealed the existence of a core set of regions that processes social rules in general comprising judgments of conventional and moral rules and that reflects valence-based decision-making [ 15 ]. However, judgments of the two types of social rules also involved differential responsiveness of cerebral areas, supporting the theoretical distinction between moral and conventional rules.…”
Section: Introductionmentioning
confidence: 99%